POTENSI JAMU SEBAGAI OBAT HERBAL ASLI INDONESIA UNTUK MENINGKATKAN DAYA TAHAN TUBUH - Aji Firda Lia F; Chaerul Fadly Mochtar; Diana Indri Sulistia; Sekar Ayu Kumara; Shella Carlina Tasya; Hasyrul Hamzah; Muh Irham Bakhtiar; Mochtar Luthfi; Chaerul Mundzir (Universitas Majalengka, 2022)
The virus that is currently endemic throughout the world is the Covid-19 virus. Covid-19, which was declared a pandemic by WHO on March 11, 2020, can enter the human body through the mucosa of the eyes, nose and mouth. The number of victims infected with the Covid-19 corona virus is increasing every day in Indonesia. One of the innovations in preventing the corona virus is the use of herbal ingredients to maintain body resistance in the New Normal period . This can keep the body healthy and fit, and can prevent and kill harmful bacteria in the body. So that the immune system will increase. Examples of the use of herbal ingredients, namely temulawak, turmeric and ginger, can be used as raw materials for herbal medicine or herbal medicine. The activity is expected to increase the knowledge of the community and students regarding the potential use of herbal medicine, an Indonesian herbal medicine to increase endurance. The method used is online via Zoom Meeting using the speaker presentation method to the participants. The results of the activity, namely consuming herbs, Indonesian herbs can help increase body resistance in the New Normal period.